Success of Systemic Methotrexate Administration Versus Laparoscopic Salpingostomy in Ectopic Pregnancy - Eryılmaz, Özlem Gün; Moraloğlu, Özlem; Seçkin, Kerem Doğa; Yeral, Mahmut İlkin and Sucak, Ayhan and Gülerman, Hacer Cavidan (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: In this study, we tried to compare the efficacies of laparoscopic salpingostomy and medication with a single dose of Methotrexate (50mg/m2) in ectopic pregnancy to determine the differences between the two methods in terms of treatment outcomes. STUDY DESIGN: In this study, 64 patients with ectopic pregnancy who had been administered an MTX therapy between August 2007 and July 2010 (Group A) were compared with another 64 patients with matching ages who had undergone a laparoscopic salpingostomy (Group B). The two groups were compared in terms of age, gravida, parity, initial hCG value, hCG measured at the time of being discharged from the hospital, hCG values checked a week later and the number of hospitalization days. The number of repeating doses and the rate of undergoing a laparoscopy salpingostomy were calculated in patients receiving MTX. RESULTS: The hCG values of the patients in the MTX and laparoscopy groups respectively were as follows: Initial hCG measurement; 670.5±1027.5 vs. 5511.3± 7293.0 (p=0.0001), hCG measured at the time of discharge; 352.3±627.0 vs. 869.7±599.1 (p=0.016), and hCG value after a week; 292.5±617.4 vs 864.1±1531.8 (p=0.023). The difference in the number of hospitalization days between the two groups came out to be significant; 2.4±4.2 for the MTX group and 1.3±1.6 for the laparoscopy group with p=0.01. Repetition of the dose became necessary in 14.1% (9/64) of the patients receiving medical treatment (MTX) as their hCG values did not decrease. Success was achieved in treating 4.7% (6/64) of these patients after the second dose and the rate of undergoing a laparoscopic salpingostomy due to MTX failure was calculated to be 4.6%. CONCLUSION: We found in this study that MTX used as a medical treatment in ectopic pregnancy was as successful as a laparoscopic salpingostomy. MTX failure can be minimized by firmly determining the criteria for the patients who will be given a medical treatment.